Hubungan Antara Kontrol Diri dan Dukungan Sosial Teman Sebaya Dengan Prokrastinasi Akademik Pada Siswa Kelas XI SMA Negeri 14 Kota Semarang - Muhammad Eka Bhayu Firmansyach; Wiwik Kusdaryani; Farikha Wahyu Lestari (Departement of Mathematics Education, 2023)
This type of research is a quantitative research with a correlational research design. The population of this study was students of class XI SMA Negeri 14 Semarang City with a total of 287 students. Class XI MIPA 5 with a total of 36 students was used for the tryout. The sample in this study were 244 students of class XI SMA Negeri 14 who were taken using simple random sampling technique. The data collection tool used is a research scale in the form of a questionnaire using the Google Form. Based on the results of the study the following conclusions can be drawn: the first hypothesis obtained a coefficient of -0.623 with a significance value of 0.000 (p <0.05) which means that there is a significant negative relationship between self-control and academic procrastination in students. while in the second hypothesis by calculating the partial influence test a correlation coefficient of -0.390 was obtained with a significance value of 0.000 (p <0.05) which means that there is a significant negative relationship between peer social support and academic procrastination in students. Testing the third hypothesis is known to show a significant result of 0.000 (p <0.01) with a regression Fcount of 123.673 meaning that there is a significant relationship between peer social support and self-control with academic procrastination with an R value of 0.711.